Constraining dust extinction properties via the VVV survey - Majaess, Daniel; Dékány, István (Arxiv, 2016)
Near-infrared color-excess and extinction ratios are essential for establishing the cosmic distance scale and probing the Galaxy, particularly when analyzing targets attenuated by significant dust. A robust determination of those ratios followed from leveraging new infrared observations from the VVV survey, wherein numerous bulge RR Lyrae and Type II Cepheids were discovered, in addition to $BVJHK_{s}(3.4→22)μ m$ data for classical Cepheids and O-stars occupying the broader Galaxy. The apparent optical color-excess ratios vary significantly with Galactic longitude ($\ell$), whereas the near-infrared results are comparatively constant with $\ell$ and Galactocentric distance ($\langle E(J-\overline{3.5μ m})/E(J-K_s) \rangle =1.28±0.03$). The results derived imply that classical Cepheids and O-stars display separate optical trends ($R_{V,BV}$) with $\ell$, which appear to disfavor theories advocating a strict and marked decrease in dust size with increasing Galactocentric distance. The classical Cepheid, Type II Cepheid, and RR Lyrae variables are characterized by $\langle A_{J}/E(J-K_s) \rangle = \langle R_{J,JK_s} \rangle =1.49±0.05$ ($\langle A_{K_s}/A_J \rangle =0.33±0.02$), whereas the O-stars are expectedly impacted by emission beyond $3.6 μ m$. The mean optical ratios characterizing classical Cepheids and O-stars are approximately $\langle R_{V,BV} \rangle \sim3.1$ and $\langle R_{V,BV} \rangle \sim3.3$, respectively.
Gesehen am 30.10.2017